Consumer Protection Act 1999 and fair trade practices in Malaysia - Amin, Naemah (2014)
This presentation aims to provide participants with information regarding the protection provided under the Consumer Protection Act 1999, among others: protection of buyers / consumers specifically in the auto – sector and in general expensive consumer product like household electrical and electronic appliances;prompt replacements for defective products OR services especially for car owners (including car parts and accessories) and other Acts and Regulations in Malaysia which will be affected if lemon law is to be included.